The history of the social sciences since 1945 - Backhouse, Roger, 1951-; Fontaine, Philippe, 1960- (Cambridge : Cambridge University Press, 2010)
This compact volume covers the main developments in the social sciences since the Second World War. Chapters on economics, human geography, political science, psychology, social anthropology, and sociology will interest anyone wanting short, accessible histories of those disciplines, all written by experts in the relevant field; they will also make it easy for readers to make comparisons between disciplines. A final chapter proposes a blueprint for a history of the social sciences as a whole. Whereas most of the existing literature considers the social sciences in isolation from one other, this volume shows that they have much in common; for example, they have responded to common problems using overlapping methods, and cross-disciplinary activities have been widespread.
Introduction / Roger E. Backhouse and Philippe Fontaine -- Psychology / Mitchell G. Ash -- Economics / Roger E. Backhouse -- Political science / Robert Adcock and Mark Bevir -- Sociology / Jennifer Platt -- Social anthropology / Adam Kuper -- Human geography / Ron Johnston -- Toward a history of the social sciences / Roger E. Backhouse and Philippe Fontaine.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Social sciences -- History -- 20th century